KUALITAS SELAI LEMBARAN LABU KUNING (Cucurbita moschata Duch. ex Poir.) DENGAN PENAMBAHAN EKSTRAK ASAM JAWA (Tamarindus indica) - Pranata, Sinung (Universitas Pelita Harapan, 2019)
Tamarind is fruit that has an acid pH that support the gel formation process. Processed products that require acid to make the structure of the gel are sheet fruit leather. Tamarind extract will produce a product that is less attractive in terms of taste or color, so it needs to be combined with pumpkin which has a yellow color. Tamarind and pumpkin are foods that have high antioxidant content which is very beneficial for the body. This aims to find out the effect of adding tamarind extract (Tamarindus indica) to the manufacture of pumpkin fruit leather (Cucurbita moschata Duch. Ex Poir.) so that it can produce the best and most preferred physical, chemical, microbiological and organoleptic fruit leather. The design of the study is completely randomized design (RAL) with 4 factor that is (100 % pumpkin : 0 % extract of tamarind), A (87,5 % pumpkin : 12,5% extract of tamarind), B (75 % pumpkin : 25 % extract of tamarind) and C ( 68,5 % pumpkin : 32,5 % extract of tamarind). The parameters tested were water content, ash content, crude fiber content, soluble fiber content, total dissolved solids, titrated acid total, total phenolic, antioxidant activity, product hardness, product color, total plate number, yeast mold, and organoleptic test. The results showed that there were significantly different effects on the quality of fruit leather which included water content testing, ash content, total dissolved solids, crude fiber test, soluble fiber test, total titrated acid, total phenolic test, antioxidant test, texture and color, but did not give a significantly different effect in terms of microbiological tests in the form of total plate numbers (ALT) and yeast molds. The quality of pumpkin fruit leather with the addition of the best tamarind extract is the treatment C ratio of 62.5% pumpkin: 37.5% extract of tamarind, both in terms of the best quality in terms of chemical, physical, microbiological and organoleptic.